Reduced Transverse Relaxation Rate (RR2) for Improved Sensitivity in Monitoring Myocardial Iron in Thalassemia - Cheung, Jerry S. (2011)
PURPOSE: To evaluate the reduced transverse relaxation rate (RR2), a new relaxation index which has been shown recently to be primarily sensitive to intracellular ferritin iron, as a means of detecting short-term changes in myocardial storage iron produced by iron-chelating therapy in transfusion-dependent thalassemia patients. MATERIALS AND METHODS: A single-breathhold multi-echo fast spin-echo sequence was implemented at 3T to estimate RR2 by acquiring signal decays with interecho times of 5, 9 and 13 ms. Transfusion-dependent thalassemia patients (N = 8) were examined immediately before suspending iron-chelating therapy for 1 week (Day 0), after a 1-week suspension of chelation (Day 7), and after a 1-week resumption of chelation (Day 14). RESULTS: The mean percent changes in RR2, R2 and R2* off chelation (between Day 0 and 7) were 11.9±8.9%, 5.4±7.7% and −4.4±25.0%; and, after resuming chelation (between Day 7 and 14), −10.6±13.9%, −8.9±8.0% and −8.5±24.3%, respectively. Significant differences in R2 and RR2 were observed between Day 0 and 7, and between Day 7 and 14, with the greatest proportional changes in RR2. No significant differences in R2* were found. CONCLUSION: These initial results demonstrate that significant differences in RR2 are detectable after a single week of changes in iron-chelating therapy, likely as a result of superior sensitivity to soluble ferritin iron, which is in close equilibrium with the chelatable cytosolic iron pool. RR2 measurement may provide a new means of monitoring the short-term effectiveness of iron-chelating agents in patients with myocardial iron overload.